Turismo e imaginário : o percurso histórico do chocolate em Gramado/RS - Vargas, Daniela Pereira de (My University, 2014)
The chocolate is a food wide consumed in many countries, as much in hot climates as cold, is consumed in liquid or solid form. Its history retraces to the pre-Columbian people, but, in 1527, the cacao seeds had been taken from Europe. In the nineteenth century they’ve created equipments to improve the visual aspect and the flavor of Chocolate and the same century they’ve opened the first factories of Chocolate in Europe. In Brazil, the first factories were opened in the late nineteenth and earlier twentieth century by European immigrants. In the south of Brazil, the presence of the chocolate is an outstanding commercial form is in Gramado (RS), from 1975, with the inauguration of the first homemade Chocolate factory. Today, the product is one of the representations of the city, the opinion before mentioned reflects in its association to the tourism in the Region. Therefore, the study is characterized by its qualitative exploratory character, having for general objective to reconstruct the description of the presence of the Chocolate in Gramado (RS) between 1975 and 2012, as an imaginary product and, in its local association to the tourism. As specific objective of the proposed dissertation contextualize historically the presence of Chocolate in Gramado / RS and theoretically contextualize the imaginary in its bond with the local tourism. As methodology, the study is made by oral history, with support of the bibliographical and documentary research. The research identified that the product appeared of a proposal brought from Argentina for Jayme Prawer. With the introduction of this product, Gramado starts to play Argentinian imagery associated with the product, and around an imaginary Chocolate Product sophisticated for elite consumption and home production. With elapsing of the years it starts to construct on the Chocolate an imaginary European and it works as homade form. At the moment that adopts the themig concept, it passes the presence of an imaginary of Disneyworld. Today, the two lines of imaginary are strong presence in the Chocolate of Gramado and the city: of Europeanization and of Disneyfication. The survey also showed that the imaginary of Chocolate feed the local tourism.
O chocolate é um alimento largamente consumido em muitos países, tanto em climas quentes como frios, na forma líquida ou sólida. A sua história remonta aos povos pré-colombianos, mas, em 1527, as sementes de cacau foram levadas para a Europa. No século XIX há a criação de equipamentos para melhorar o aspecto visual e o sabor do chocolate e a abertura, na Europa, das primeiras indústrias produtoras de chocolate. No Brasil, as primeiras fábricas foram inauguradas no final do século XIX e início do século XX, por imigrantes europeus. No Sul do Brasil, a presença do chocolate de forma comercial marcante se dá na cidade de Gramado (RS), a partir de 1975, com a inauguração, no local, da primeira fábrica de chocolate caseiro. Hoje, o produto é uma das representações do município e está consolidado no imaginário das pessoas, o que se reflete na sua associação com o turismo na região. Logo, o estudo se caracteriza por seu corte qualitativo e por seu caráter exploratório, tendo por objetivo geral reconstruir o histórico da presença do chocolate em Gramado (RS) entre os anos 1975 a 2012, como produto e imaginário, na sua associação local com o turismo. Como objetivos específicos, a dissertação propôs contextualizar historicamente a presença do chocolate em Gramado (RS) e contextualizar teoricamente os imaginários no seu vínculo com o turismo no local. Como metodologia, o estudo utilizou a história oral, com apoio das pesquisas bibliográfica e documental. A pesquisa identificou que o produto surgiu de uma proposta trazida da Argentina por Jayme Prawer. Com a introdução desse produto, Gramado passa a reproduzir o imaginário argentino associado ao produto, e em torno do chocolate, um imaginário de produto sofisticado, para um consumo de elite e de produção caseira. Com o decorrer dos anos passa a construir sobre o chocolate um imaginário europeu e a trabalhá-lo na forma artesanal. No momento que adota o conceito de tematização, passa-se à presença de um imaginário disneyficado. Hoje, as duas linhas de imaginário estão fortemente presentes no chocolate de Gramado e no município: o de europeização e o de disneyficação. A pesquisa também mostrou que os imaginários do chocolate alimentam o turismo local.
Keywords: Turismo - Gramado (RS); Chocolate - Gramado (RS)